The fate of liberty : Abraham Lincoln and civil liberties - Neely, Mark E. (Oxford University Press, 1991)
The Fate of Liberty is a comprehensive look at the issues of civil liberties during Lincoln's administration, placing them in the political context of the time. It examines the practical impact on civil liberties of the policies Lincoln developed to save the Union. Neely focuses on Lincoln's suspension of the writ of habeas corpus in a turbulent time of unforeseen events that threatened the stability of the nation - the threat to Washington as Maryland flirted with secession, disintegrating public order in the border states, corruption among military contractors, contraband trade with the South and the outcry against the first draft in United States history. Drawing upon letters from prisoners, records of military courts and federal prisons, memoirs, and federal archives, he paints a vivid picture of how Lincoln responded to these problems, how his policies were actually executed, and the virulent political debates that followed.